Prevalence of Bovine Schistosomiasis and Associated Risk Factors in Tis Abay District, Northwest Ethiopia - Temesgen Kifle; Tirumengist Bayile; Haben Fesseha; Mesfin Mathewos (Veterinary Medicine International)
Background. Schistosomiasis is a parasitic disease of cattle that is caused by trematode worms and results in morbidity, mortality, reduced fertility, and productivity. Methods. A cross-sectional study was conducted to determine the prevalence and associated risk factors for bovine schistosomiasis in Tis Abay district, Amhara, Ethiopia. Fecal samples were collected from 384 randomly selected cattle and examined using the sedimentation technique. Results. Of the total examined fecal samples, 13.02% (50/384) of the samples were positive for Schistosoma bovis eggs. The prevalence of schistosomiasis was highly reported in Dasra (22.4%), which was statistically significant (p≤0.001). The prevalence of bovine schistosomiasis was higher in females (16.9%), crossbred cattle (17.1%), poorly conditioned cattle (37.1%), extensively managed cattle (17.9%), and cattle greater than 5 years old (23.1%). The multivariate analysis of factors revealed that study area, age, breed, body condition, and management system have a significant role (p<0.05) in the prevalence of bovine schistosomiasis. Conclusion. Schistosoma infection is a problem for cattle in the study region. Therefore, farmers should be aware of the transmission of the disease, prevention, and control of snails.